Therapeutic effect of fecal microbiota transplantation on hyperuricemia mice by improving gut microbiota - Yuan, Songjian; Jia, Wenting; Liu, Xiaomei; Liu, Ruzhen; Cao, Man; Wu, Yuting; Li, Yuantao; Xu, Wei; Xiao, Chuanxing; Hong, Zhenqiang; Zhang, Bangzhou (Frontiers in Microbiology, 2025)
ObjectiveThe primary objective of this study was to assess the impact of fecal microbiota transplantation (FMT) on serum biochemical parameters, renal injury, and gut microbiota in hyperuricemia (HUA) mice.MethodsSix-week-old male C57BL/6 J mice were given a high-purine diet and potassium oxonate injections to induce HUA, followed by a two-week FMT treatment. Regular body weight checks, serum biochemical analyses, and fecal sampling for 16S rRNA gene sequencing were conducted to evaluate the treatment’s impact on gut microbiota.ResultsThe model group showed significant increases in uric acid (UA), creatinine (Cr), blood urea nitrogen (BUN) levels, and increased xanthine oxidase (XOD) activity compared to controls (p < 0.05). FMT treatment effectively reduced these levels and XOD activity (p < 0.05). At the genus level, specific taxa like Muribaculaceae and Prevotellaceae_UCG-001 were less abundant, while Blautia and Ruminiclostridium_9 were more abundant in the model group. Following FMT, gut microbiota composition returned to near-normal levels, with significant differences from the model group (p < 0.05).ConclusionThis study demonstrates that FMT holds therapeutic potential for HUA mice by reducing UA levels, alleviating renal damage, and restoring gut microbiota balance.